'Iraqi' cinema since the US-led invasion of 2003. Issue 3 (1st September 2016) - Ginsberg, Terri
During the 1950–70s, film production in Iraq was relatively prolific. Private industry eventually gave way to nationalization under Ba'th Party rule. Not unlike Iraqi cinema of the colonial era, most post-independence Iraqi cinema had the ideological aim of propping up the new regime while supplying light entertainment to the populace. A minor auteur cinema did develop, which produced a small number of critical independent films, but the movement was short-lived. The bulk of quality film production in Iraq occurred during the period of nationalization. This development eventually led to the establishment of a film school in Baghdad. Since the Iran–Iraq War, national film production in Iraq effectively ended. This is not to say that films publicized as 'Iraqi' have not been produced in recent years; on the contrary, a small but noteworthy number of 'Iraqi' films have been made, primarily for international distribution, largely by Iraqi ex-patriots to (and from) Europe and with financial support from private foreign sources. This article discusses two such films, Zaman: The Man from the Reeds (Alwan, 2003), and Ahlaam (al-Daradji, 2006), comparing and contrasting their differing but overlapping strategies, which evidence the suffering of Iraqis living under conditions of war and violence. These strategies at the same time in varying ways distract or distort attention from the real determinants of those conditions. By extension the article draws critical connections between the aims and orientations of new 'Iraqi' cinema and the hasbara cultural initiatives of contemporary Israel.